Role of finish lines design on stress distribution in fixed partial denture - Felix Hartanto Ongko; Syafrinani; Putri Welda Utami Ritonga (Indonesia Prosthodontic Association, 2022)
All-ceramic restorations have been widely used in prosthodontics as metal-free restoration because of their esthetics, biocompatibility, and inert properties. However, fracture remains a complication for all-ceramic restorations. All-ce-ramic posterior restorations encounter significant fracture after 5 years of usage than anterior region. Stress distri-tribution in all-ceramic restorations during mastication is higher on cervical margin than other surfaces according to finite element analysis. Shoulder and chamfer finish line are recommended designs for maximum fracture resist-ance of restoration and had influence in stress distribution. Mechanical properties of restoration material such as flex-ural strength, modulus of elasticity (ME), and fracture resistance are important factors that must be considered for its durability. Increasing ME of restoration material will increase strength of fracture. Zirconia usually used because of its superior fracture resistance among other ceramic material (ME±205 GPa). Shoulder is recommended in zir-conia because of greater fracture resistance but other literature suggests chamfer. Lithium disilicate has an improved physical properties and translucency ceramic restoration and is recommended as an alternative treatment (ME±96 GPa). In lithium disilicate, shoulder and chamfer have almost equal fracture resistance. PEEK is a thermoplastic semi-crystalline material with ME near human cortical bone (±3.6 GPa) with shock absorption properties. This litera-ture review role of all-ceramic restoration finish lines design on stress distribution. Shoulder and chamfer still the main choice in FPD but which design is most appropriate still undecided.